Murine interleukin 2 receptor beta chain: dysregulated gene expression in lymphoma line EL-4 caused by a promoter insertion. - Kono, T (1990)
The functional, high-affinity interleukin 2 receptor (IL-2R) consists of at least two receptor components, IL-2R alpha (p55) and IL-2R beta (p70-75). The cDNA encoding the murine IL-2R beta has been isolated by using the previously cloned cDNA for human IL-2R beta as a probe. Analysis of the cDNA revealed that the murine IL-2R beta shows a marked homology with the human IL-2R beta and that it is also structurally related to other cytokine receptors such as erythropoietin receptor. The cDNA-directed murine IL-2R beta formed high-affinity IL-2R in conjunction with the endogenous IL-2R alpha in a murine pro-B-cell line and could transduce IL-2-induced growth signal. In mouse lymphoma line EL-4, the IL-2R beta gene was found to be rearranged by the insertion of the long terminal repeat sequence of an intracisternal A particle, giving rise to constitutive expression of the IL-2R beta mRNA.